Frontline Science: Defects in immune function in patients with sepsis are associated with PD-1 or PD-L1 expression and can be restored by antibodies targeting PD-1 or PD-L1 - Patera, Andriani C. (J Leukoc Biol, 2016)
Sepsis is a heterogeneous syndrome comprising a highly diverse and dynamic mixture of hyperinflammatory and compensatory anti-inflammatory immune responses. This immune phenotypic diversity highlights the importance of proper patient selection for treatment with the immunomodulatory drugs that are entering clinical trials. To better understand the serial changes in immunity of critically ill patients and to evaluate the potential efficacy of blocking key inhibitory pathways in sepsis, we undertook a broad phenotypic and functional analysis of innate and acquired immunity in the same aliquot of blood from septic, critically ill nonseptic, and healthy donors. We also tested the ability of blocking the checkpoint inhibitors programmed death receptor-1 (PD-1) and its ligand (PD-L1) to restore the function of innate and acquired immune cells. Neutrophil and monocyte function (phagocytosis, CD163, cytokine expression) were progressively diminished as sepsis persisted. An increasing frequency in PD-L1(+)-suppressor phenotype neutrophils [low-density neutrophils (LDNs)] was also noted. PD-L1(+) LDNs and defective neutrophil function correlated with disease severity, consistent with the potential importance of suppressive neutrophil populations in sepsis. Reduced neutrophil and monocyte function correlated both with their own PD-L1 expression and with PD-1 expression on CD8(+) T cells and NK cells. Conversely, reduced CD8(+) T cell and NK cell functions (IFN-γ production, granzyme B, and CD107a expression) correlated with elevated PD-L1(+) LDNs. Importantly, addition of antibodies against PD-1 or PD-L1 restored function in neutrophil, monocyte, T cells, and NK cells, underlining the impact of the PD-1:PD-L1 axis in sepsis-immune suppression and the ability to treat multiple deficits with a single immunomodulatory agent.